Effect of green building features on energy efficiency of university buildings in tropical climate - Ahamed Zacki; Shakila Pathirana (Sustainable Futures)
The construction sector significantly contributes to global environmental issues, including excessive energy use and carbon emissions. Green building practices have emerged as a key strategy to enhance energy efficiency and sustainability. This study evaluates the impact of selected green building features on the energy performance of a university laboratory building located in Sri Lanka. Using DesignBuilder simulation software, the energy-saving potential of features such as LED lighting, double-glazed glass, sunshades, green roofs, and green walls was assessed. Financial feasibility was evaluated using Life Cycle Cost Analysis (LCCA) and Benefit-Cost Ratio (BCR). Results show that LED lighting achieved the highest energy savings (6.04%) and the most favorable BCR (51.08), followed by double-glazed glass (3.88% savings, BCR = 16.79) and sunshades (3.23% savings, BCR = 44.90). While green roofs and walls provided moderate energy benefits, they offered substantial environmental advantages such as urban heat island mitigation. The study recommends prioritizing cost-effective measures like LED lighting and double glazing in university retrofits, and it highlights the need for future research on integrating multiple green features and expanding simulations to varied climatic zones.